PENGARUH PROMOSI JABATAN, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KARYAWAN PADA PT. HADJI KALLA CABANG URIP SUMOHARJO DI MAKASSAR - Ali Baba (Jurnal Bisnis dan Kewirausahaan, 2017)
This study aims To determine and analyze the influence of promotion position, work environment and compensation affect the employee job satisfaction at PT. Hadji Kalla Branch Urip Sumoharjo in Makassar. Sampling technique is by distributing questionnaires to employees who met at the Office of PT. Hadji Kalla Branch Urip Sumoharjo in Makassar are willing to fill out the research questionnaire .. The sample of 32 respondents and analyzed by using multiple regression analysis. Based on the results of this study concluded that promotion positions, work environment and compensation affect employee work satisfaction at PT. Hadji Kalla Branch Urip Sumoharjo in Makassar